Calibrated ages of Kohala peat core from Big Island, Hawaii, USA - David W Beilman (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.